A cardiac fibroblast-enriched micropeptide regulates inflammation in ischemia/reperfusion injury - Youchen Yan; Tingting Zhang; Xin He; Tailai Du; Gang Dai; Xingfeng Xu; Zhuohui chen; Jialing Wu; Huimin Zhou; Yazhi Peng; Yan Li; Chen Liu; et al. (JCI Insight, 2025)
Inflammation is a critical pathological process in myocardial infarction. Although immunosuppressive therapies can mitigate inflammatory responses and improve outcomes in myocardial infarction, they also increase the risk of infections. Identifying novel regulators of local cardiac inflammation could provide safer therapeutic targets for myocardial ischemia/reperfusion injury. In this study, we identified a previously unknown micropeptide, which we named Inflammation Associated MicroPeptide (IAMP). IAMP is predominantly expressed in cardiac fibroblasts, and its expression is closely associated with cardiac inflammation. Down-regulation of IAMP promotes, whereas its overexpression prevents, the transformation of cardiac fibroblasts into a more inflammatory phenotype under stressed/stimulated conditions, as evidenced by changes in the expression and secretion of pro-inflammatory cytokines. Consequently, loss of IAMP function leads to uncontrolled inflammation and worsens cardiac injury following ischemia/reperfusion surgery. Mechanistically, IAMP promotes the degradation of HIF-1α by interacting with its stabilizing partner HSP90, and thus suppresses the transcription of pro-inflammatory genes downstream of HIF-1α. This study underscores the significance of fibroblast-mediated inflammation in cardiac ischemia/reperfusion injury and highlights the therapeutic potential of targeting micropeptides for myocardial infarction.